Проблемні питання визначення суспільно небезпечних наслідків самоправства - Чернов, А.; Chernov, А. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджуються питання визначення та конкретизації змісту суспільно небезпечних наслідків самоправних дій у ст. 356 КК України. Встановлено, що поняття «значна шкода», як суспільно небезпечний наслідок самоправства, не містить нормативного визначення у нормах КК України, а також кількісного обрахування. За наслідками аналізу судової практики констатовано, що відповідне поняття не розкривається у судовій практиці вищих судових інстанцій України. Запропоновано критерії розмежування самоправства за ознаками суспільно небезпечного наслідку злочину з відповідним адміністративним правопорушенням. In the article questions of definition and specification of the content of socially dangerous consequences of arbitrary actions in the article 356 of the Criminal Code of Ukraine have been investigated. It has been established that the concept of «significant damage» as socially dangerous consequence of arbitrariness, does not contain normative definition in norms of the Criminal Code of Ukraine, and quantitative calculation either. According to the results of the analysis of court practice it has been noted that the corresponding concept is not revealed in court practice. Criteria of differentiation of arbitrariness according to signs of socially dangerous consequence of a crime with the corresponding administrative offence have been suggested. For the purpose of legislative definition of the concept of «significant damage» of material aspect it has been offered to supplement the article 356 of the Criminal Code of Ukraine with the note according to which considerable harm, if it implies causing material damage, means such harm which in hundred and more times exceeds free minimum of the income of citizens. Definition of the concept of «significant damage to interests of the citizen, state or public interests or interests of the owner» also has to be concretized according to immaterial forms of socially dangerous consequences for ensuring legal definiteness of the law of Ukraine on criminal responsibility.
Problematic Issues of Definition of Socially Dangerous Consequences of Arbitrariness
Keywords: суспільно небезпечний наслідок; значна шкода; громадський та державний інтерес; адміністративне правопорушення; оціночне поняття; кримінально-правова кваліфікація; socially dangerous consequence; significant damage; public and state interest; administrative offence; estimated concept; criminal and legal qualification